2021
DOI: 10.1039/d1qo00018g
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt- and iron-catalyzed regiodivergent alkene hydrosilylations

Abstract: A complementary set of base metal catalysts has been developed for regiodivergent alkene hydrosilylations: iron complexes of amine-iminopyridine ligands are selective for Markovnikov hydrosilylations (branched/linear up to >99:1), while the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…This result is in good agreement with the results described in previous reports on the activation of Fe and Co complexes by NaO t Bu. 23,24 Since first row transition metal complexes with carboxylato ligands such as [LM(OC(O)R) 2 ] have been reported to show catalytic activity for hydrosilylation without an activator, 13,16,19,27 we investigated the catalytic activity of [Co(tpy)Br 2 ] in the presence of potassium pivalate (KOPv) and found that KOPv effectively activated [Co(tpy)Br 2 ] (entries 5 and 6). It should be noted that a carboxylate anion can activate the Co complex, whether it is used as a ligand for the complex or added externally.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is in good agreement with the results described in previous reports on the activation of Fe and Co complexes by NaO t Bu. 23,24 Since first row transition metal complexes with carboxylato ligands such as [LM(OC(O)R) 2 ] have been reported to show catalytic activity for hydrosilylation without an activator, 13,16,19,27 we investigated the catalytic activity of [Co(tpy)Br 2 ] in the presence of potassium pivalate (KOPv) and found that KOPv effectively activated [Co(tpy)Br 2 ] (entries 5 and 6). It should be noted that a carboxylate anion can activate the Co complex, whether it is used as a ligand for the complex or added externally.…”
Section: Resultsmentioning
confidence: 99%
“…Relatively air-stable alkoxide salts such as NaO t Bu were reportedly good activators. [23][24][25] According to the proposed mechanism, an alkoxide nucleophilically attacks hydrosilane (HSiR 3 ) to form a silicate species [HSiR 3 (X)] − (Fig. 1), and the silicate exhibits reducing power (or hydride properties) to form an active species from the precatalyst [LMX 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there are more and more reports on alkene hydrosilylation catalyzed by base metals such as iron, [4][5][6][7][8][9] cobalt [9][10][11][12][13][14][15][16][17] and nickel. [18][19][20][21][22] However, in the construction of a ligand skeleton, most catalysts are metal complexes supported by bidentate ligands 6,16,20 or pincer ligands ([NNN], 7,18,19 [NNP] 4,5 [CNC] 11 and [PSiP] 13,14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the synthesis of benzylic silanes was a representative example. The most important synthetic method of benzylic silanes was transition-metal-catalyzed Markovnikov-type hydrosilylation of vinylarenes, including Co-, Fe-, Ni-catalyzed hydrosilylation of vinylarenes (Scheme , 2a) . In addition, transition metal catalyzed cross-coupling between α-heteroatom-substituted benzyl hydrocarbons and silicon nucleophiles can also be used for the preparation of benzylic silanes (Scheme , 2b) .…”
Section: Introductionmentioning
confidence: 99%